Effect of Extreme Heatwaves on the Mortality and Cellular Immune Responses of Purplish Bifurcate Mussel Mytilisepta virgata (Wiegmann, 1837) (=Septifer virgatus) in Indoor Mesocosm Experiments - Hong, Hyun-Ki; Kim, Chang Wan; Kim, Jeong-Hwa; Kajino, Nobuhisa; Choi, Kwang-Sik (Frontiers in Marine Science, 2021)
In the rocky intertidal environment, the frequency and duration of heatwaves have increased over the last decade, possibly due to global climate change. Heatwaves often result in lethal or sub-lethal disturbances in benthic animals by changing their metabolic activities. In this study, we investigated the impacts of extreme heatwave stress on the hemocyte functions of Mytilisepta virgata and subsequent mortality to gain a better understanding of the potential causes and consequences of mass mortality events in this mussel during summer. We discriminated three types of hemocytes in the hemolymph, granulocytes, hyalinocytes, and blast-like cells, using flow cytometry and revealed that granulocytes were the major hemocyte involved in cellular defensive activities, such as phagocytosis and reactive oxygen species (ROS) production. For the experiment, mussels were exposed to a 40°C air temperature for 12 h per day over 5 days under laboratory conditions as a simulated semi-diurnal tidal cycle. Mortality began to occur within 3 days after beginning the experiment, and all mussels had died by the end of the experiment. Flow cytometry indicated that the mussels exposed to high air temperatures produced significantly more ROS than did the control mussels within 2 days after the onset of the experiment, which may have caused oxidative stress. Such high levels of ROS in the hemolymph increased DNA damage in hemocytes after 3 days of exposure and decreased the phagocytosis of hemocytes 4 days after the experiment began. The observed mortality and decline in immune capacity suggested that an extreme heat event occurring in the rocky intertidal ecosystem during summer could exert sublethal to lethal impacts on macrobenthic animals.